Executing the National Curriculum of Digital Citizenship Education in the Country of Georgia (Global Journal of Human-Social Science, 2024)
The international events of recent years have provided us with a new perspective on citizenship in the modern world where the borderlines between online and real life are erased and blurred To navigate safely and ethically in the online space it is essential to integrate digital citizenship education into curricula not only at the national level but also at the level The present study aims to collect the subjective evaluations and positions of the school community regarding the implementation of educational innovation in general education in particular the digital citizenship curriculum Critical and curriculum research approaches were used within the research An in-depth interview and focus group are used as a research method Five school principals and fifty-five teachers participated in the research Based on the study results the following conclusions are drawn Georgia s general education system should create conditions for schools to select the programmed one the adaptive-evolutionary one or the hybrid one - which would be more effective at a specific school and which approach would facilitate achieving the best results Each school should be given freedom in the implementation process and supported with recommended methodological guidelines and guides for the successful implementation of the curriculum The school principal should understand their responsibility for implementing innovations support teachers to the maximum extent and care not only about individual teachers but also about systemic and strategic change to achieve sustainable and long-term educational transformation Recent international events have underscored the critical importance of digital citizenship education in navigating the increasingly interconnected world where online and offline boundaries are blurred
Keywords: educational changes; digital citizenship education; curriculum implementation; critical theory; curriculum studies